Remote bednet use monitoring to describe patterns of use and exposure to female Anopheles mosquitoes in an Ugandan cohort - Krezanoski, Paul J.; Rek, John; Musiime, Alex; Otto, Geoffrey; Kyagamba, Patrick; Rwatooro, Jackson Asiimwe; Walters, Kelly; Romanel, Alina; Arinaitwe, Emmanuel; Nankabirwa, Joaniter I.; Drakeley, Chris J.; Kamya, Moses; et al. (Frontiers in Epidemiology, 2022)
Background Long lasting insecticide-treated bednets (LLINs) are the most widely used tool for preventing malaria. There has been a plateau in progress in the highest burden African countries since 2015, raising questions about the effectiveness of LLINs. In this study, remote LLIN use monitors were deployed in a cohort in Uganda to explore how LLIN use interacts with mosquito exposure. Methods The SmartNet study included 20 households from May to October 2019. SmartNet devices recorded, every 15 minutes, whether an LLIN was unfurled or folded up. Unannounced visits were used to assess SmartNet accuracy. Risk factors associated with poor LLIN use were assessed using generalized linear equations. Female Anopheles exposure was estimated by combining hourly probabilities of exposure from human landing catches and measures of density from biweekly CDC light traps in participants rooms. Mosquito exposure averted by LLINs was quantified using SmartNet measurements and age-related differences were estimated using generalized linear equations, adjusting for covariates and household clustering. Results 96 individuals contributed 5,640 SmartNet observation nights. In 126 unannounced visits, SmartNet had an area under the curve of 0.869 in classifying whether the LLIN was up or down. The rate of non-use was 13.5% of nights (95% CI: 12.6 to 14.3%). Compared to children under 5, non-use was 1.8 times higher (95% CI: 1.6 to 2.1; p<0.001) in children 5-15 years and 2.6 times higher (95% CI: 2.2 to 3.1; p<0.001) in participants 15-<30years. There was no difference between children under 5 years and adults >30 years. LLIN use averted 50.3% of female Anopheles mosquito exposure (95% CI: 40.0% to 60.0%), with decreasing efficacy across age groups: from 61.7% (95% CI: 42.6% to 80.7%) in children under 5 years to 48.0% (95% CI: 29.1% to 66.8%) in adults over 30. Conclusions Objective monitors are accurate and can feasibly be deployed to obtain data about LLIN use. LLINs provided protection from only 50% of female Anopheles mosquito exposure in this cohort and protection was dependent upon age. In assessing the role of LLINs in malaria prevention it is crucial to consider the dynamics between mosquito exposure and LLIN use behaviors.